Three- hop Distributed Routing Protocol for Hybrid Network - jacob, Judith; koyakutty, Shinu (IJRDO -Journal of Computer Science Engineering, 2015)
Hybrid wireless networks combining the advantages of both mobile ad-hoc networks and infrastructure wireless networks .Network simply combine ad-hoc transmission mode with cellular transmission mode. Distributed Three-hop Routing protocol (DTR) for hybrid wireless networks take full advantage of the widespread base stations, DTR divides a message data stream into segments and transmits the segments in a distributed manner. Furthermore, sending segments to a number of base stations simultaneously increases throughput and makes full use of widespread base stations. DTR significantly reduces overhead due to short path lengths and the elimination of route discovery and maintenance. DTR also has a congestion control algorithm to avoid base stations overload. DTR in comparison with other routing protocols in terms of throughput capacity, scalability and mobility resilience. Data splitting based on Chinese remainder theorem will reduce data loss and lost data can be recollected.